Comparison of the effect of terlipressin and albumin on arterial blood volume in patients with cirrhosis and tense ascites treated by paracentesis: a randomised pilot study. Issue 1 (1st January 2002) - Moreau, R; Asselah, T; Condat, B; de Kerguenec, C; Pessione, F; Bernard, B; Poynard, T; Binn, M; Grangé, JD; Valla, D; Lebrec, D
Abstract : Background: Patients with cirrhosis and tense ascites treated by paracentesis alone have a decrease in effective arterial blood volume after ascites removal. Although intravenous albumin is effective in preventing paracentesis induced decreased arterial blood volume, its clinical use is controversial. As paracentesis induces arteriolar vasodilation which plays a role in the development of decreased effective arterial blood volume, administration of a vasoconstrictor (terlipressin) could prevent circulatory alterations due to paracentesis. Aims: To perform a pilot study comparing the effects of terlipressin and albumin on effective arterial blood volume in patients with cirrhosis treated by paracentesis for tense ascites. Methods: Twenty patients with cirrhosis and tense ascites were randomly assigned to be treated by either paracentesis and terlipressin or paracentesis and albumin. Terlipressin (3 mg) or albumin (8 g/l of removed ascites) were administered on the day of paracentesis. Effective arterial blood volume was assessed by measuring plasma renin concentrations at baseline and on the day of hospital discharge (4–6 days after treatment). Decreased effective arterial blood volume was defined as an increase in plasma renin concentrations on the day of hospital discharge of more than 50% of baseline values. Results: Irrespective of the treatment group, mean values for plasma renin concentrations at hospital discharge did not differ from their respective baseline values (p=0.10). Baseline plasma levels of renin concentrations did not differ between the terlipressin and albumin groups (p=0.61). Changes from baseline in plasma renin concentrations did not differ between groups (p=0.39). Three patients in the terlipressin group and three in the albumin group developed decreased arterial blood volume. Conclusions: This randomised pilot study suggests that terlipressin may be as effective as intravenous albumin in preventing a decrease in effective arterial blood volume in patients with cirrhosis treated by paracentesis for tense ascites.